Iron and manganese fluxes across the sediment-water interface in a drinking water reservoir. (1st September 2020) - Krueger, Kathryn M.; Vavrus, Claire E.; Lofton, Mary E.; McClure, Ryan P.; Gantzer, Paul; Carey, Cayelan C.; Schreiber, Madeline E.
Abstract: The development of low dissolved oxygen (DO) concentrations in the hypolimnion of drinking water reservoirs during thermal stratification can lead to the reduction of oxidized, insoluble iron (Fe) and manganese (Mn) in sediments to soluble forms, which are then released into the water column. As metals degrade drinking water quality, robust measurements of metal fluxes under changing oxygen conditions are critical for optimizing water treatment. In this study, we conducted benthic flux chamber experiments in summer 2018 to directly quantify Fe and Mn fluxes at the sediment-water interface under different DO and redox conditions of a eutrophic drinking water reservoir with an oxygenation system (Falling Creek Reservoir, Vinton, VA, USA). Throughout the experiments, we monitored DO, oxidation-reduction potential (ORP), water temperature, and pH in the chambers and compared the metal fluxes in the chambers with time-series of fluxes calculated using a hypolimnetic mass balance method. Our results showed that metal fluxes were highly variable during the monitoring period and were sensitive to redox conditions in the water column at the sediment-water interface. The time-series changes in fluxes and relationship to redox conditions are suggestive of "hot moments", short time periods of intense biogeochemical cycling. Although the metal concentrations and fluxes are specific to this site, the approaches for examining relationships between metals, oxygen concentrations and overall redox conditions can be applied by water utilities to improve water quality management of Fe and Mn. Graphical abstract: Image 1 Highlights: We measured metal fluxes across sediment-water interface of a eutrophic reservoir. Fluxes (Fe, Mn) were measured under different redox conditions using two methods. Time series of fluxes were highly variable, reflecting hot moments of metal cycling. Fluxes were sensitive to hypolimnetic oxygen and redox potential (ORP). Under anoxic conditions, ORP is a useful indicator of metal fluxes.